Quality of colonoscopy in children with rectal bleeding in Egypt - Ahmed S Gado; Basel A Ebeid; Aida M Abdelmohsen; Ayman E Eskander; Anthony T Axon (SpringerOpen, 2015)
Background Colonoscopy is the diagnostic evaluation of choice in cases of rectal bleeding (RB). Colonoscopy in children is different from that in adults, but the technique of the examination is similar. Colonoscopy is a technically demanding procedure with the potential for harm if performance is unsatisfactory, and thus assurance of quality is pivotal. A colonoscopy quality-assurance program was instituted in 2003. Aim The aim of this study was to determine the quality of colonoscopy in children with RB after introducing a colonoscopy quality-assurance program. Patients and methods The study was cross-sectional and hospital-based. It was undertaken between 2010 and 2013 on 107 children who underwent colonoscopy for the evaluation of RB. Results A total of 112 colonoscopies were assessed. A diagnosis was established in 69 (62%) colonoscopies and polyps were detected in 52%. Cecal intubation was achieved in 107 (90%). The main reason for an unsuccessful cecal intubation was poor bowel preparation. The adjusted completion rate was 97%. The mean time to reach the cecum was 16 min. The mean time for completion of the procedure was 31 min. Colon preparation was rated adequate in 63 (56%) colonoscopies. A total of 119 polyps were detected in 58 colonoscopies, with an average of two polyps per colonoscopy (range 1-7). In all, 113 polyps were excised. All polyps were judged to be completely removed in 52 (95%) colonoscopies. Polypectomy was not performed in three colonic examinations with solitary polyps. Five (4%) patients had postprocedural vomiting. There was one (1%) sedation-related complication (respiratory distress), but no procedure-related complications or mortality. Conclusion A high standard of colonoscopy in children with RB can be achieved by introducing a colonoscopy quality-assurance program.